Current Status, Opportunities and Challenges of Cottage and Small Scale Industries - Kharel, Khom Raj (Economic Journal of Nepal, 2005)
Industrialization plays a crucial role in the process of economic development. National income, per capita income, output and employment can grow at a faster rate only through development of industries of various sizes. In the context of Nepal, cottage and small scale industrial sector deserves priority as an instrument of industrialization because Nepal is facing the problem of high population growth rate, unemployment, income inequalities etc. Although large and medium scale industries also generate more employment opportunities they require comparatively heavier amount of capital, which is generally scarce in Nepal. It is necessary to make our industrialization process dynamic and consolidated by developing and expanding cottage and small-scale industries in keeping with our limited markets, level of technical know-how, position of transportation, and the geographical structure of the country. There are great possibilities of establishing cottage and small-scale industries utilizing the existing local resources due-to geological and geophysical structure of the country. By the development of cottage and small scale industries, it will be enhanced to achieve the target of poverty reduction from 38 to 30 percent. The main objective of this study is to analysis current status, opportunities and challenges of cottage and small-scale industries in Nepal. Economic Journal of Nepal Vol.28(4) 2005 pp.257-263